Pembuatan ADC (Analog to Digital Converter) Untuk Rancang Bangun Instrumentasi Temperatur Tinggi Menggunakan Prinsip Defleksi Laser He-Ne Sebagai Bagian Dari Sistem Kendali Operasi Di Bidang Industri - Kadarisman, Nur; Sumarna, Sumarna; Rosana, Dadan (BERKALA FISIKA, 2010)
Monitoring and control all process variables such as power, temperature, and pressure is an absolute necessity in the field of industry. Instrumentation is a tool that can be used to monitor and control the process variables. From the monitoring results it can be seen whether the system is running in accordance with the desired or not. If deviation occurs, then the control action is needed so that the process can run as expected (the operating control system). One of the instrumentation equipment that need to be investigated is the use of laser deflection, because the laser beam that has a coherent nature, so that this instrumentation can be a very useful tool in the industry. At that stage the second year of this research study focused on the process input and data analysis with the aid of a microcontroller as a stage before applied in the modeling industry. The study was conducted in two stages, namely the manufacture of the ADC program that can send data voltage to the computer via RS 232 serial cable and making the ADC data acquisition software in the computer so the computer can act as a collection station, storage, and display data. This software use Borland Delphi 7. The results showed that the graph can be known voltage variations can indicate changes in certain deflection. The value of this deflection will determine the temperature of which is shown by the graph. Changes in the analog signal from the source of the potentiometer into a digital signal using ADC is inversely proportional, which is indicated by a linear graph with a correlation R = 0.99079 Graph showing the relationship between deflection with temperature according to the graph of the results of previous years of research that is done manually. Thus, further stay pending the outcome of the development of an acceptable deflection pattern detector equipped with a data acquisition system, as the final stage before implemented in the industry. Data acquisition system consists of two parts: signal conditioning systems and interfaces. If the detector is subjected by a laser beam, the optical signal is converted into electrical signals. This causes an electrical current. Because the electric current generated by the detector is very small, it needs to be strengthened and transformed into voltage by a signal conditioning system.Temperatures are measured in a particular room will cause the laser beam deflection at a certain distance so it can be used for high temperature control system. Keywords: ADC, Instrumentation, He-Ne Laser, Borland Delphi